1987
DOI: 10.1007/bf01421824
|View full text |Cite
|
Sign up to set email alerts
|

Formamide, a water substitute XIV (1) waterless microemulsions 8. Structural analysis by X-ray scattering of CTAB aggregates in formamide and in the microemulsion system (formamide, CTAB, isooctane, 1-butanol)

Abstract: X-ray scattering was used to analyse the structures of aggregates of CTAB in various formamide-containing media.Firstly, CTAB micelles were detected in formamide solutions. A spherical micelle model was proposed; at values close to the CMC, smaller micelles were observed in formamide than in water.Secondly, the structure of microemulsions in the isooctane-rich zone of the system (formamide/CTAB = 2, isooctane, 1-butanol) was studied by X-ray scattering. The structure was found to be quite different in this zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Micelle and liquid crystal formation has been reported in solvents such as ethylene glycol (EG) [15], glycerol [2,16,[26][27][28], formamide [4,[17][18][19][20][21]29], and hydrazine [22,23]. The glycol solvents have high cohesive energies and dielectric constants (ε r (EG) = 53 and ε r (PG) = 30), and hydrogenbonding properties, which are believed to be essential requirements for promoting micellization [24].…”
Section: Introductionmentioning
confidence: 98%
“…Micelle and liquid crystal formation has been reported in solvents such as ethylene glycol (EG) [15], glycerol [2,16,[26][27][28], formamide [4,[17][18][19][20][21]29], and hydrazine [22,23]. The glycol solvents have high cohesive energies and dielectric constants (ε r (EG) = 53 and ε r (PG) = 30), and hydrogenbonding properties, which are believed to be essential requirements for promoting micellization [24].…”
Section: Introductionmentioning
confidence: 98%
“…Microemulsions were formulated by replacing water with other nonaqueous polar solvents such as formamide (FA), N,N -dimethyl formamide (DMF), ethylene glycol (EG), propylene glycol (PG), and glycerol (GLY) [20][21][22][23][24][25][26][27][28][29][30][31]. Among these, much attention has been focused on FA, since it is sparingly soluble in oils and its presence decreases the hydrophobicity of the surfactants [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…There has recently been much research dealing with the effects of nonaqueous polar solvents on the formation of cationic micelles (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Micel!e or liquid crystal formation has been reported to occur in such solvents as hydrazine (3,4), glycerol (5,6), ethylene glycol (7,8), and formamide (9)(10)(11)(12)(13)(14)(15)(16)(17)(18), where all of the aforementioned solvents have high cohesive energy, dielectric constant, and a high degree of hydrogen bonding. Evans and co-workers (19) have indicated that the ability of a solvent to form hydrogen bonds is a necessary condition of micelle formation.…”
Section: Introductionmentioning
confidence: 99%